Evaluating Foreign Tourists’ Attitude in Tourism Discourses: How Foreign Tourists Negotiated Their Affect, Judgement, and Appreciation on Indonesian Cultural Elements - Suroto Suroto; Anit Pranita Devi (E-Structural (English Studies on Translation, Culture, Literature, and Linguistics), 2022)
Abstract. This study focused on evaluating how foreign tourists negotiate their affect, judgement, and appreciation. The attitudes of foreign tourists were analyzed using appraisal theory. This study applied qualitative descriptive paradigm to describe the phenomenon of language practice in the field of tourism. Video recordings showing the interactions between the foreign tourists and the interviewer were translated and analyzed. From the total of 107 clauses, 31 clauses that contained Indonesian cultural elements and appraising items were selected. The results show that the dominant cultural elements found in the interaction are in the form of living equipment especially various kinds of Indonesian traditional foods. Other cultural elements are in the form of art and knowledge. In negotiating the cultural elements, the foreign tourist expresses their attitude both positively and negatively. Attitude in the subtype of affect consists of five positive affects: four in the form of happiness expressions and one desire expression. Further, the negative affect is not found. The subtype of judgement consists of one negative normality and one positive normality, respectively. Attitude in the subtype of appreciation consists of sixteen positive valuations and eight negative valuations.Keywords: appraisal; attitude; affect; appreciation; judgementAbstrak. Penelitian ini difokuskan untuk mengevaluasi bagaimana wisatawan mancanegara menegosiasikan perasaan (affect), penilaian (judgment), dan apresiasi (appreciation) mereka. Sikap wisatawan mancanegara dianalisis dengan menggunakan teori appraisal. Penelitian ini menggunakan paradigma deskriptif kualitatif untuk mendeskripsikan fenomena praktik bahasa di bidang pariwisata. Rekaman video yang menunjukkan interaksi antara turis asing dan pewawancara ditranskripsi dan dianalisis. Dari total 107 klausa, dipilih 31 klausa yang mengandung unsur budaya Indonesia dan penanda appraisal. Hasil penelitian menunjukkan bahwa unsur budaya dominan yang ditemukan dalam interaksi tersebut berupa peralatan hidup khususnya berbagai jenis makanan tradisional Indonesia. Unsur budaya lainnya adalah berupa seni dan pengetahuan. Dalam menegosiasikan unsur-unsur budaya, wisatawan mancanegara mengungkapkan sikapnya baik positif maupun negatif. Sikap dalam subtipe affect terdiri atas lima affect positif yang meliputi empat ekspresi kebahagiaan (happiness) dan satu buah eskpresi keinginan (desire). Adapun sikap affect negatif tidak ditemukan. Sikap dalam subtipe judgement terdiri atas satu normalitas negatif dan satu normalitas positif. Sikap dalam subtipe appreciation terdiri atas enam belas valuasi positif dan delapan valuasi negatif.Kata kunci: appraisal, affect, appreciation, judgement, sikap